The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1111/j.1745-4530.1998.tb00443.x
|View full text |Cite
|
Sign up to set email alerts
|

RESIDENCE TIME DISTRIBUTION (RTD) AND GOODNESS OF MIXING (GM) DURING CO2‐INJECTION IN TWIN‐SCREW EXTRUSION PART II: GM STUDIES

Abstract: Experimental residence‐time distribution (RTD) characteristics of an extrusion process may be used to estimate the extent of mixing experienced in the extruder. Using earlier theories of laminar mixing and striation thickness reduction, a new approach to estimate efficacy of mixing of two phases in the mixing zone of the extruder is proposed. Predicting the time required to achieve complete mixing and comparing it with the minimum time (plug flow time) that the extrudate spends in the mixing zone gives a ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Rizvi and co-workers have developed several processes using a co-rotating twin screw extruder with a 52 mm screw diameter (Wenger TX52) [25,26,[45][46][47][48][49][50][51][52][53][54][55][56][57]. The screw configuration and L/D ratio were varied according to the application.…”
Section: Experimental Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rizvi and co-workers have developed several processes using a co-rotating twin screw extruder with a 52 mm screw diameter (Wenger TX52) [25,26,[45][46][47][48][49][50][51][52][53][54][55][56][57]. The screw configuration and L/D ratio were varied according to the application.…”
Section: Experimental Devicesmentioning
confidence: 99%
“…During extrusion of breakfast cereals, Rizvi et al were mainly interested in the characterization of the mixing between this foodstuff and sc-CO 2 . First, they investigated the residence time distribution (RTD) of a dye injected by means of CO 2 [50], and then porosity was examined by image analysis [51]. The RTD of a reactor is a probability distribution function that describes the amount of time a fluid element spends inside the reactor [67].…”
Section: Foodstuffsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ollett and others (1989) showed that MRT decreased from about 80 s at 75 rpm to 40 to 50 s at 300 rpm. Singh and Rizvi (1998b) showed that average residence time decreased sharply from 119.2 s to 80.8 s when screw speed was increased from 150 to 200 rpm, but decreased only moderately from 80.8 s to 74.8 s when the screw speed was further increased from 200 rpm to 250 rpm.…”
Section: Effects Of Screw Speedmentioning
confidence: 99%
“…With this model a fairly close simulation of the RTD could be made. Singh and Rizvi (1998b) modeled exit age distributions, E-curves using the approach of Wolf-White model, a cascade of CSTRs. and a plug-flow in series with CSTR model.…”
Section: Modeling Residence Time Distribution and Mean Residence Timementioning
confidence: 99%